NURSING PRACTICES IN MENTAL HEALTH IN THE FAMILY HEALTH STRATEGY: AN INTEGRATIVE REVIEW - Ana Monalisa Ferreira Merces; Bruna de Medeiros Leite Souza; Tatiane Lins da Silva; Thassia Thame de Moura Silva; Ana Márcia Tenório de Souza Cavalcanti (Universidade Federal do Paraná, 2015)
This integrative review aims to identify the nurse's practices in mental health in the Family Health Strategy. The search for data was undertaken in the period 29th May - 10th June 2014, in the following databases: the Latin American and Caribbean Center on Health Sciences Information, International Literature in Health Sciences, the Brazilian Nursing Database (BDENF) and in the Biomedical Literature Citations and Abstracts. A total of nine articles was found, distributed in three categories: Difficulties and the need for training in Mental Health, Main practices in nursing for the person with mental disorders and the Family Health Strategy: Member of the Mental Health Network. It is concluded that the nurses working in this scenario position their practices in Mental Health based in embracement, in renewing prescriptions, in dispensing drugs and in referral to specialized services. These attitudes, however, are recognized as insufficient in Mental Health care.